2011
DOI: 10.1124/jpet.111.184200
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Brain Barrier (BBB) Pharmacoproteomics: Reconstruction of In Vivo Brain Distribution of 11 P-Glycoprotein Substrates Based on the BBB Transporter Protein Concentration, In Vitro Intrinsic Transport Activity, and Unbound Fraction in Plasma and Brain in Mice

Abstract: The purpose of this study was to examine whether in vivo drug distribution to the brain can be reconstructed by integrating P-glycoprotein (P-gp)/mdr1a expression levels, P-gp in vitro activity, and drug unbound fractions in mouse plasma and brain. For 11 P-gp substrates, in vitro P-gp transport activities were determined by measuring transcellular transport across monolayers of mouse P-gptransfected LLC-PK1 (L-mdr1a) and parental cells. P-gp expression amounts were determined by quantitative targeted absolute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(147 citation statements)
references
References 30 publications
5
139
1
2
Order By: Relevance
“…In SIL methods such as the absolute quantification (AQUA) method (30), the IS is commonly spiked during or postdigestion and is the most feasible and rapid approach. Indeed, SIL peptides are among the most common IS used to evaluate the expression of drug transporters (5)(6)(7)18,19,(46)(47)(48)(49)(50)(51). A comparison of the SIL peptide with SILAM approach was recently carried out in the LC-MS/ MS method development in our laboratory (37).…”
Section: Selection Of Internal Standard (Is)mentioning
confidence: 99%
“…In SIL methods such as the absolute quantification (AQUA) method (30), the IS is commonly spiked during or postdigestion and is the most feasible and rapid approach. Indeed, SIL peptides are among the most common IS used to evaluate the expression of drug transporters (5)(6)(7)18,19,(46)(47)(48)(49)(50)(51). A comparison of the SIL peptide with SILAM approach was recently carried out in the LC-MS/ MS method development in our laboratory (37).…”
Section: Selection Of Internal Standard (Is)mentioning
confidence: 99%
“…In some cases, transport parameters were first verified in isolated microvessels (closest to the in vivo situation), and then studied in cell culture systems 76,61 . Molecular biology research has allowed the characterization of gene and protein expression in isolated microvessels and low passage endothelial cell cultures from the same species, and between different species, most often from small animals such as rodents (mice and rats) or from cow and pig in comparison to humans 77,78,75,15 . Transcriptomic comparison between in vivo and in vitro brain microvascular endothelial cells showed numerous gene transcripts that were differentially expressed and most often significantly downregulated in vitro.…”
Section: Molecular and Functional Characterizationmentioning
confidence: 99%
“…3) to take account of the unbound fractions of P-gp/mdr1a substrates in plasma (f u,plasma ) and brain (f u,brain ) (Uchida et al, 2011a).…”
Section: Prediction Of Bbb P-gpmentioning
confidence: 99%
“…Using normal mice as a model, we have previously demonstrated that the K p brain ratio can be reconstructed using the equation presented below (eq. 2) from the in vitro P-gp/mdr1a efflux activity (in vitro P-gp efflux ratio) and protein expression levels of P-gp/mdr1a in mouse P-gp/mdr1a-transfected LLC-PK1 cell monolayer and isolated mouse brain capillaries, according to in vivo reconstruction theory (Uchida et al, 2011a). …”
Section: Prediction Of Bbb P-gpmentioning
confidence: 99%
See 1 more Smart Citation